Pengaruh Massa dan Waktu Kontak Terhadap Penyerapan Ion Logam Pb2+ Menggunakan Xerogel dari Abu Kulit Durian (Durio zibethinus Murr.) - Putri, Sinta Eka; Nasra, Edi; Sanjaya, Hary; Riga, Riga (Periodic, 2024)
Lead metal is one of the hazardous metals produced from industrial activities in Indonesia and can pollute the environment. The maximum level of Pb2+ ions in waters is 0.03 mg/L. If the Pb2+ ion level exceeds the predetermined level, it will have a harmful effect on the environment and living things. Adsorption is a method that can be used to reduce lead metal levels in water. The adsorbent that can be used is xerogel, which produced from durian peel (Durio zibethinus Murr.). The purpose of this study is to determine the optimum conditions of absorption and determine the absorption capacity of xerogel from durian peel against Pb metal. In this study, the batch method was used for the adsorption process by varying contact time and adsorbent contact mass. The results of this study obtained the absorption capacity under the optimum conditions of contact time of 60 minutes, and an adsorbent mass of 0.2 grams of 6.04 mg/g.